Implementasi Value Stream Mapping (VSM) untuk Mengurangi Waste dalam Produksi Precast di CV. ABC - Alfan, Muhammad; Hamidah, Nur (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
CV. Abc is a company that produces precast concrete. By using the Value Stream Mapping (VSM) method, which is a visualization method used in Lean Manufacturing to identify, analyze and improve the flow of material and information in a production process. This research aims to evaluate how wasteful precast concrete products are. CV. Abc works in the field of infrastructure development, especially irrigation and making products such as U-dith, Box Culvert, and Cover. The results of the research were carried out by dividing 7 waste into 7 types of waste based on the level of importance and performance. This research found that there is waste that needs to be corrected, especially related to visual defects on the product surface. Recommendations for improvement include better waste control, better finishing processes, and more efficient production processes. It is hoped that the implementation of these measures will increase customer satisfaction and increase the company's competitiveness in the construction market.